APPLICATION OF INVENTORY METHOD IN IMPROVING STUDENT LEARNING ACTIVITIES ON NATURAL RESOURCES SUMMARY AND ENVIRONMENTAL ENVIRONMENT - Aqmarina Dewi (IKIP Siliwangi, 2017)
The main issues of this research are how to improve the learning activity of Elementary School students on Natural Resources (NR) and Environment (EN) subject matter through the method of discovery. The objectives of the research are as follows: (1). Increase the learning activity of elementary students through discovery method; (2). Provides learning through discovery methods that enhance learning activities. The methods / approaches used in achieving the following objectives: (a). Collect students and elementary teachers involved in research; (B). Provide an overview of the research activities to be undertaken; (C). Reflecting on, discussion of learning by method of discovery; (D). Collaborate with elementary teachers in the determination of experimental class and control class; (E). Implementation of learning method of discovery; (F). Evaluation of learning by method of discovery. The results showed that there was an increase in learning activity of elementary school students through learning by inventory method of 34%; (2). Elementary students are enthusiastic about learning by the method of discovery given by the teacher; (3). The occurrence of collaboration between one student and another student at the time of learning by the method of discovery is done. Keywords: Learning Activity, Discovery Method.